(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. This article discusses the morphological and physiological structure of the male and female reproductive systems of rabbits, their role in reproduction, the period of sexual maturity, and their specific features in reproductive activity. Rabbits are characterized by a high level of reproduction , which requires an in-depth study of their reproductive system.